Impact of Learning a Foreign Language on the Enhancement of Cognitive Functions Among Healthy Older Population - Valis, Martin; Slaninova, Gabriela; Prazak, Pavel; Poulova, Petra; Kacetl, Jaroslav; Klimova, Blanka (Journal of psycholinguistic research, 2019)
The purpose of this article is to discuss to what extent foreign language learning may enhance cognitive functions among healthy older population. The methods used in this study included cognitive assessments using standardized tests, intervention through English language teaching and learning, and statistical analysis. Out of 60 older Czech citizens, 42 cognitively unimpaired participants were selected for the experiment. These participants were randomly divided into an experimental group (20 subjects) studying English for 12 weeks (three 45-min lessons per week) and a control group (22 subjects) whose members did not have any language training. The results of the research show that there has been a slight enhancement of cognitive skills in the experimental group. Nevertheless, on the whole, the scores of the experimental and control groups did not considerably differ. Despite this fact, the results indicate that cognitive functions among healthy older population can be maintained through regular foreign language training.
Keywords: senioři; Healthy older individuals; kognice; Multilingualism; mnohojazyčnost; stárnutí; Limitations; Aging; Effect; Humans; učení; Cognition; Aged; Cognitive functions; English language learning; Cognitive decline; lidé; Learning